The Covid 19 Outbreak and the Importance of Health Literacy (Turkey Health Literacy Journal, 2020)
In the history of the humanity, many pandemics occured that have resulted in the downfall of health, social and economic sides. The Covid-19 pandemic have occured in the beginning of the 2020 and a vaccination or a treatment have not been found yet. The fact that it has been 11 months since the first case, and there is still no cure to this disease shows the importance of protection and preventation precautions. The preventation of the transmission of the virus is possible by the individuals learning the ways of spreading and breaking the chain of the transmission individually, rather than the persistance of the protecters and the deterrent applications. And this highlights the health literacy.